2013
DOI: 10.1016/j.socscimed.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Child health in the United States: Recent trends in racial/ethnic disparities

Abstract: In the United States, race and ethnicity are considered key social determinants of health because of their enduring association with social and economic opportunities and resources. An important policy and research concern is whether the U.S. is making progress toward reducing racial/ethnic inequalities in health. While race/ethnic disparities in infant and adult outcomes are well documented, less is known about patterns and trends by race/ethnicity among children. Our objective was to determine the patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 61 publications
2
73
0
Order By: Relevance
“…Farley and Haaga 2005; Mehta et al 2013). Because they are ubiquitous to life in America, many people assume that a person's race and ethnicity are stable and essential characteristics.…”
Section: Introductionmentioning
confidence: 98%
“…Farley and Haaga 2005; Mehta et al 2013). Because they are ubiquitous to life in America, many people assume that a person's race and ethnicity are stable and essential characteristics.…”
Section: Introductionmentioning
confidence: 98%
“…They have a higher risk of being born preterm or postterm, having respiratory allergies, or having an adverse cardiovascular risk profile [Mehta et al, 2013;Gishti et al, 2015;Khanolkar et al, 2015]. Moreover, differences in oral health among ethnic groups have been reported by various studies from the Netherlands and other parts of the world [Truin et al, 2010;Wigen and Wang, 2010;Guarnizo-Herreño and Wehby, 2012;Schuller et al, 2014;Matsuo et al, 2015].…”
mentioning
confidence: 99%
“…Therefore, an examination of negative children's health outcomes in the United States may be warranted to investigate moderate to severe risk factors which may be associated with specific preventable health issues and disease prevalence rates among American Children. Mehta, Lee, and Ylitalo (2013) found that children residing in both low and middle-income households are more susceptible to preventable diseases, racial and ethnic disparities when seeking quality healthcare, and higher rates of illnesses. Additionally, there may be a growing effort to explore additional factors which may also attribute to poor health among children's groups.…”
Section: Introductionmentioning
confidence: 99%